2013
DOI: 10.1016/j.mri.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase and ATP synthase reaction rates in human frontal lobe measured by 31P magnetization transfer spectroscopy at 4T

Abstract: The human frontal lobe is critical for cognitive function in the healthy brain. Many psychiatric disorders including schizophrenia and bipolar disorder are associated with apparent mitochondrial dysfunction and bioenergetic abnormalities in the frontal lobe. Therefore, measuring cerebral bioenergetics associated with creatine kinase (CK) and ATP synthase reactions could provide crucial information regarding the underlying molecular mechanisms associated with psychiatric disorders. In this study, the unidirecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
4
18
1
Order By: Relevance
“…b–b). The resultant T 1 , k , and σ parameters are consistent with the findings in human brains by long‐TR band inversion approaches and by ST , as compared in Table . Except for the ER matrix A (Eq.…”
Section: Discussionsupporting
confidence: 84%
“…b–b). The resultant T 1 , k , and σ parameters are consistent with the findings in human brains by long‐TR band inversion approaches and by ST , as compared in Table . Except for the ER matrix A (Eq.…”
Section: Discussionsupporting
confidence: 84%
“…31P-Magnetic resonance spectroscopy (31P-MRS) was used to measure brain ATP levels as described in previous studies 3840 with modifications. Briefly, the mice under the control condition or isoflurane anesthesia were gently restrained to a plastic warm water bag (37 C°) in prone position, using paper tape.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we applied a BISTRO saturation scheme with significantly improved saturation profile . Previously, we demonstrated that the RF spillover effect is negligible during the use of the BISTRO saturation scheme with control spectrum acquired in the absence of RF saturation at 9.4T and 4T . Therefore, we believe only two 31 P spectra (control and saturation of γ‐ATP resonance) are required to determine forward reaction kinetics of CK/ATPases reactions in vivo at high/ultra‐high field scanner ( ≥ 4T).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo 31 P spectra were processed using the jMRUI software package (http://www.mrui.uab.es/mrui/mrui_Overview.shtml). The peak integrals of PCr, γ‐ATP, and Pi resonance were quantified by spectral fitting with the AMARES algorithm, as described in detail previously . All simulations in this study were performed using in‐house written MATLAB software (R2009b, Mathworks Inc, Natick, MA).…”
Section: Methodsmentioning
confidence: 99%